2010
DOI: 10.1016/j.bpj.2009.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Basis for the Mesoscopic Extensibility of Dendrimer-Compacted DNA

Abstract: The mechanism of DNA compaction by dendrimers is key to the design of nanotechnologies that can deliver genetic material into cells. We present atomistic simulations, mesoscopic modeling and single-molecule pulling experiments describing DNA dendrimer interactions. All-atom molecular dynamics were used to characterize pulling-force-dependent interactions between DNA and generation-3 PAMAM amine-terminated dendrimers, and a free energy profile and mean forces along the interaction coordinate are calculated. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 48 publications
1
32
0
Order By: Relevance
“…The types of guest molecules considered in this review will include low molecular weight organic molecules [24,29,50,51], and nucleic acids [38,[69][70][71][72][73]. The review of interactions of dendrimers with lipid membrane has been clearly explained in Reference [37].…”
Section: The Physical Properties Of Complex Systems Of Dendrimers Witmentioning
confidence: 99%
See 1 more Smart Citation
“…The types of guest molecules considered in this review will include low molecular weight organic molecules [24,29,50,51], and nucleic acids [38,[69][70][71][72][73]. The review of interactions of dendrimers with lipid membrane has been clearly explained in Reference [37].…”
Section: The Physical Properties Of Complex Systems Of Dendrimers Witmentioning
confidence: 99%
“…The free energies of the complex showed that the binding strength increases with higher generation of dendrimer and that the binding energy per protonated primary amine (dendrimer) was maximized for the G4 dendrimer, suggesting that the G4 dendrimer could be the optimum candidate for gene therapy applications. Mills et al performed molecular dynamics simulations with the CHARMM 27 force field to study the binding between a dendrimer and dsDNA [70]. In this work, the local environment effects, such as deformation and the electrostatic interactions, were characterized and related to single molecule pulling experiments.…”
Section: The Physical Properties Of Complex Systems Of Dendrimers Witmentioning
confidence: 99%
“…This difference between the two different orientations has been quantified in our previous work. 54 Close to the DNA (see the 20–30 Å range), the two orientations lead to different PMF profiles because the binding geometry is different. However, at distances farther from the DNA (beyond 30 Å), the two orientations lead to essentially the same curves.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] Latest researches have been performed to carry dendrimers and biological macromolecules (DNA or oligonucleotide) complexes into cells without damaging or deactivating DNA fragments. [26][27] Moreover, Shcharbin et al 28 predicted that phosphorus-containing dendrimers would be wonderful gene carrier in the future.…”
Section: Gene Vectormentioning
confidence: 99%